Markers for DNA damage are induced in the rat colon by the Alternaria toxin altertoxin-II, but not a complex extract of cultured Alternaria alternata - Aichinger, Georg; Pahlke, Gudrun; Puntscher, Hannes; Groestlinger, Julia; Grabher, Stephanie; Braun, Dominik; Tillmann, Katharina; Plasenzotti, Roberto; Del Favero, Giorgia; Warth, Benedikt; Höger, Harald; Marko, Doris (Frontiers in Toxicology, 2022)
Mycotoxins produced by Alternaria spp. act genotoxic in cell-based studies, but data on their toxicity in vivo is scarce and urgently required for risk assessment. Thus, this study assessed their DNA-damaging potential in liver and colon tissue of Sprague-Dawley rats. Animals received single doses of a complex Alternaria toxin extract (CE; 50 mg/kg bw), altertoxin II (ATX-II; 0.21 mg/kg bw) or vehicle by gavage, one of the most genotoxic metabolites in vitro and their tissues were collected after 3 or 24 h, respectively. Western Blot analysis revealed a significant increase of histone 2a.X phosphorylation and depletion in the colon of rats that received ATX-II 24 h before sampling. Applying RT-PCR array technology we identified genes of interest for qRT-PCR testing, which confirmed an induction of Rnf8 transcription in the colon of the 3 h ATX-II and the 24 h CE group. Transcription of Cdkn1a was diminished in the 24 h ATX-II group, possibly indicating tissue repair after chemical injury. In contrast to the observed response in the colon, no markers for genotoxicity were induced in the liver of treated animals. We hereby provide the first report of ATX-II as a genotoxicant in vivo. Deviating results for similar concentrations of ATX-II in a natural Alternaria toxin mixture argue for substantial mixture effects. These results call for a profound human risk assessment of ATX-II and similar perylene quinones produced by Alternaria molds.